Analisis Teks “ Rupa Allah “ Menurut Surat Filipi 2 : 6 Dan Kitab Kejadian 5 : 1 - 3 - Dolfie Lumimpah (EUANGGELION: Jurnal Teologi dan Pendidikan Kristen, 2021)
The article contains an analytical study of the text "The form of God" according to Philippians 2: 6 and Genesis 5: 1 - 3, whether it has the same meaning based on semantic studies. This study aims to enrich the biblical treasures and to strengthen biblical theological understanding based on analysis of course. The author uses a narrative and structural analysis method with a semantic observation approach to the sentence or text "Rupa Allah" according to Philippians 2: 6 and Genesis 5: 1 - 3. With the fact that the sentence or text "Rupa Allah" according to Philippians 2: 6 and the Book of Genesis 5: 1 - 3, has a different meaning seen from semantic exploration, where "the image of God" according to Philippians 2: 6 is greater in the man Jesus Christ who has the essence of God, while "the image of God" according to Genesis 5: 1 - 3 more taxes on the immaterial first human. The things that are caused by humans in the image of God do not mean that they are divine. Humans were created on a lower level and depend on Allah even though it helps to use the same text.